Una recente traduzione del De civitate dei - Grossi, Vittorino (Augustinianum, 2012)
This note highlights the difficulties of reading the vocabulary of the De civitate Dei and makes annotations to the introduction of the new Italian translation of the De civitate, edited by Domenico Marafioti with an extensive introduction and notes: Sant’Agostino, La città di Dio, a cura di Domenico Marafioti, Arnoldo Mondadori Editore, Milano 2011 (Oscar Grandi Classici), 1632 pagine. ISBN 978-88-04-60888-2.